A Solid‐Solution Approach to Mixed‐Metal Metal–Organic Frameworks – Detailed Characterization of Local Structures, Defects and Breathing Behaviour of Al/V Frameworks (Eur. J. Inorg. Chem. 26/2013). Issue 26 (3rd September 2013) - Kozachuk, Olesia; Meilikhov, Mikhail; Yusenko, Kirill; Schneemann, Andreas; Jee, Bettina; Kuttatheyil, Anusree V.; Bertmer, Marko; Sternemann, Christian; Pöppl, Andreas; Fischer, Roland A.
Abstract : The cover picture shows correlations (linear as well as non‐linear) between metal ratios and the structure and properties of materials while increasing the complexity of the framework and combining different metals in single‐phased MOFs to give mixed‐metal MOF solid solutions. The applied EPR spectroscopic analysis, in particular, is a powerful tool in these studies to obtain insight into the local metal structures in such complex multicomponent MOF materials and to detect intrinsic structural defects that are not observed (and not expected) in the parent monometallic MOFs. O. K. is acknowledged for designing the cover artwork. Details are discussed in the article by R. A. Fischer et al. onp. 4546 ff . For more on the story behind the cover research, see theCover Profile .